Enablers and Barriers to Medication Self-Management in Patients With Type 2 Diabetes: A Qualitative Study Using the COM-B Model - Li H; Li Y; Wang J; Zhang Y; Ben S (Patient Preference and Adherence)
Huiqin Li,1 Ying Li,2,* Jing Wang,3,* Yuyao Zhang,1 Shiyan Ben1 1School of Nursing, Anhui University of Chinese Medicine, Hefei, People’s Republic of China; 2Clinical Pharmacy, The First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, People’s Republic of China; 3Department of Endocrinology, The First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ying Li, Jing Wang; The First Affiliated Hospital of Anhui University of Chinese Medicine, No. 117 Meishan Road, Hefei, Anhui, People’s Republic of China, Tel +86-189-1961-4050, +86-138-6619-2906, Email 1807883959@qq.com, 800wjj@163.comIntroduction: Type 2 diabetes mellitus is a chronic disease of global concern. Medication self-management is the process by which an individual actively plans, monitors, evaluates, feeds back, controls, and regulates their medication through their behavior and awareness. Patients’ medication self-management is key to glycemic control. A comprehensive understanding of the factors influencing medication self-management and the implementation of effective intervention programs is therefore paramount.Objective: To examine the enablers and barriers to medication self-management in patients with type 2 diabetes mellitus and to propose a corresponding medication self-management program to improve medication self-management.Methods: This qualitative study drew up the interview outline with reference to the COM-B model. Sampling was done using purposive sampling method and data collection was done using semi-structured interviews. The interviews mainly included patients’ challenges and facilitators in the process of medication self-management. The data were analyzed using a framework analysis method, and themes were generated using the COM-B model.Results: A total of 20 patients participated in this study. The enablers identified within the COM-B model were the policy support for medical insurance and higher medication self-efficacy. The barriers include low medication literacy, aging of body functions, changes in living habits, the impact of work, limited medical resources, misguided beliefs about medication, and emotional response. The online media applications and the impact of family and friends were mixed factors. Outside of the model, diet and exercise also have an impact. Finally, we propose targeted solutions to improve medication self-management based on the Behavior Change Wheel.Conclusion: This study proposes targeted medication self-management programs, including education interventions to improve medication literacy and self-efficacy, leveraging mobile smart devices, and improving health insurance policies to promote patient medication management levels. Our findings will contribute to medication self-management for type 2 diabetes and many more chronic diseases.Keywords: type 2 diabetes mellitus, medication self-management, enablers, barriers, qualitative study, framework analysis